Impact of Marketing Mox Towards Customer Satisfaction in Oppa K-Grill Samgyeopsal at Quezon City: An Assessment: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Having healthy eating in life is one of the fundamentals that our body needs; food becomesour comfort every time we might be having a hard time. Especially when we are diningoutside our homes, like dining in a fancy restaurant, an expensive one, unlimited, eating allyou can like a buffet, etc. Franchising your very own restaurant, like a grill, was one of thehardest things and decision-making to do. But, nowadays, Filipinos have been influenced byKorean culture, like the aforementioned “Samgyeopsal,” which was first introduced in theearly 20th century in Kaesong, South Korea, as stated by Argarin’s (2021) article.Samgyeopsal Grill restaurant has been adopted in the Philippines, and it still had asignificant number of consumers even when it first started.The result of this study is that the majority of the respondents are the younger generation,which is ages 18-35 years old, and for the civil status, most of the respondents are singleand most likely employed consumers. The variable affecting the decreasing demand andcontinuous serving was the place when it came to “Wide parking space for the customers,”which was interpreted as partly satisfied. Meanwhile, the assessment in terms of product,price, and promotion was good enough for the two groups of respondents who wereinterpreted as very satisfied. The biggest problem encountered by the two groups ofrespondents was the long waiting time within the restaurant for the customers to eat andenjoy the food because of its small waiting area for a bunch of customers that are coming.Overall, the researchers recommend that a portion of the restaurant be renovated,particularly the area where customers can come in at any moment, because the number ofcustomers may have an impact on restaurant operation.
Keywords: Business Administration